Chronic Type A Aortic Dissection: Rare Presentation of Incidental Pericardial Effusion. (2nd May 2019) - Abugroun, Ashraf; Subahi, Ahmed; Gaznabi, Safwan; Daoud, Hussein
Abstract : Aortic dissection is the most devastating sequelae of aortopathy other than aortic rupture. However, aortic dissection can be asymptomatic in the acute phase with delayed symptomatic presentation or incidental diagnosis upon chest imaging. We report a case of a 63-year-old male who was diagnosed with pericardial effusion upon preoperative workup for elective cholecystectomy. Further investigations confirmed hemorrhagic pericardial effusion secondary to a chronic dissecting ascending aortic aneurysm. The patient condition was successfully managed with open surgical repair with an uneventful postoperative course. This case demonstrates an extremely rare presentation of incidental hemorrhagic pericardial effusion caused by a chronic dissecting ascending aortic aneurysm.